2004
DOI: 10.1002/jsfa.1721
|View full text |Cite
|
Sign up to set email alerts
|

Influence of packaging material on pomegranate juice colour and bioactive compounds, during storage

Abstract: Pomegranate juices were assessed after pasteurisation and storage in different packaging materials: transparent and green glass, and paperboard carton with polyethylene layers (Minibrik-200). The main objective was to establish the influence of the container on the stability of colour and bioactive compounds (anthocyanins, ellagic acid and other non-coloured phenols). Results showed that noncoloured phenols and ellagic acid were quite stable during the storage period. In contrast, anthocyanins degraded, to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
82
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 28 publications
15
82
1
1
Order By: Relevance
“…In our study, no variations were observed in the antioxidant activity between different containers (carton, plastic and aluminium bags with and without modified atmosphere), in the deoxyribose assay and lipid peroxidation (except the vegetable flavoured soup in normal atmosphere aluminium packaging, p<0.05) in agreement with Pérez-Vicente et al (2004) who observed no differences in foods stored in glass, brik cartons and brik aluminium, and Raitio et al (2012) using containers with normal atmosphere and with MAP. However, the TEAC value of the meat flavoured and fish flavoured soups (p<0.05) was lower in plastic bag than the rest of packed.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, no variations were observed in the antioxidant activity between different containers (carton, plastic and aluminium bags with and without modified atmosphere), in the deoxyribose assay and lipid peroxidation (except the vegetable flavoured soup in normal atmosphere aluminium packaging, p<0.05) in agreement with Pérez-Vicente et al (2004) who observed no differences in foods stored in glass, brik cartons and brik aluminium, and Raitio et al (2012) using containers with normal atmosphere and with MAP. However, the TEAC value of the meat flavoured and fish flavoured soups (p<0.05) was lower in plastic bag than the rest of packed.…”
Section: Discussionsupporting
confidence: 84%
“…These values are lower than those reported by Pérez-Vicente et al (2004) (Table 2), being lower for those genotypes with pink arils that gave juices of higher pH. Tzulker et al (2007) reported values of total anthocyanin content from less than 100 to around 300 mg cyanidin-3-glucoside L -1 for juices prepared from the arils of 29 Israeli pomegranate accessions.…”
Section: Resultsmentioning
confidence: 54%
“…While a* value was 12.03 at the beginning of storage, it decreased to 6.54 at the end of 12 months storage. Perez-Vicente et al (2004) found that a* value of pomegranate juice significantly decreased during processing and storage. Another study carried out on dried persimmon by Tülek & Demiray (2014).…”
Section: Resultsmentioning
confidence: 95%